PCSK9 Promotes the Malignancy of Triple‐negative Breast Cancer Cells by Reducing Cholesterol Levels at the Plasma Membrane to Activate EGFR and HER3 - Tianhong Li; Renfei Wu; Kathy Qian Luo (Advanced Science)
Abstract Triple‐negative breast cancer (TNBC) is a highly heterogeneous and clinically aggressive disease with the highest mortality rate among all subtypes of breast cancer. To discover new driver genes for metastatic TNBC, this work compares the transcription profiles of MDA‐MB‐231‐GFP cells and 231‐GFP‐derived lung metastatic cells (4–11). Results reveal that proprotein convertase subtilisin/kexin type 9 (PCSK9) is highly upregulated in 4–11 cells. Knockdown of PCSK9 greatly decreases the tumorigenic and metastatic potential of 4–11 cells, whereas overexpression of PCSK9 significantly enhances tumor maliganancy. Mechanistically, the binding of PCSK9 to the low‐density lipoprotein receptor (LDLR) results in decreased LDLR at the plasma membrane, which further decreases cholesterol and lipid raft in the plasma membrane and activates human epidermal growth factor receptor 1 and 3 (EGFR and HER3). Subsequently, phosphorylated EGFR and HER3 activate the Src/ERK/c‐Jun to increase the levels of cyclin D3 and vimentin and thereby enhance cell growth and metastasis. Metadata analyses also reveal that TNBC patients with high PCSK9 expression exhibited worse clinical outcomes. Taken together, these findings not only reveal a novel mechanism by which PCSK9 promotes the malignant potential of TNBC but also indicate that PCSK9 is a potential therapeutic target for treating TNBC patients.